Implementasi Media Canva sebagai Sarana Edukasi Visual dalam Meningkatkan Motivasi Belajar Siswa MI Darul Hikmah Cinere - Wina Yusnaeni; Nining Suryani; Mahna Zakiah Nadhif; Amalia Indah Khairunnisa; Kayla Chika Putri Heri (Pengabdian kepada Masyarakat Bidang Teknologi dan Sistem Informasi (PETISI), 2026)
One of the key focuses of the government’s Sustainable Development Goals (SDGs) is the education sector, which includes computer education and training programs. This initiative aims to enhance knowledge and broaden public insight, particularly among children. This is important because children are in the early stages of engaging with the digital world; therefore, they need proper guidance to ensure that technology is used in a positive and beneficial manner. In today’s digital era, technology-based media provides ease of access to a wide range of information. Furthermore, individuals are able to compare information from various sources more efficiently, which contributes to a better understanding of the information obtained. However, the problem faced by students at Madrasah Ibtidaiyah Darul Hikmah is their limited knowledge in creating engaging and varied educational posters, particularly through the use of the Canva application. Therefore, a training program is needed to equip students with basic skills in designing educational posters. The expected outcomes of this activity include the publication of articles in electronic media or national websites, as well as the improvement of participants’ knowledge and skills in educational poster design. Based on these issues, training in creating educational posters is considered a relevant solution. This activity is expected to enhance students’ ability to produce creative, attractive, and diverse visual educational media.